Lecture programme
001-0097-001 EUZKO ETXEA BASQUE HOUSE. 8 CROMWELL PLACE SOUTH KENSINGTON. LONDON. S W. 7 Tel KENSINGTON 664I Continuing the series of lectures inaugurated in October, the following will be the programme for November : — 4th November, 1944. Miss F. L. JOSEPHY. (Chairman of the Executive of Federal Union) 11th November, 1944. His Excellency Sr. Don Carlos Freile Larrea. (Ecuadorian Minister) 18th November, 1944. His Excellency Sr. Don Manuel Bianchi.(Chilean Ambassador) 25th November, 1944. Sr. Don Carles Pi-Sunyer.(President of the Catalan National Council) The lectures will begin at 7 p.m. 292/946/1/97